A new modified CPW‐fed wideband circularly polarized half‐split cylindrical dielectric resonator antenna with different permittivity of two layers in radial direction. Issue 3 (3rd November 2016) - Kumar, Rajkishor; Chaudhary, Raghvendra Kumar
Abstract: In this article, a wideband circularly polarized half‐split cylindrical dielectric resonator antenna (HS‐CDRA) having two layers with different permittivity in radial direction is investigated. Designed antenna is excited by a new modified CPW fed which consists of signal line, helps to realization of circular polarization, half‐split cylindrical dielectric resonator (HS‐CDR), to confirm that circular polarization in proposed antenna. HS‐CDR is made of two different materials which can supports to enhance the input impedance bandwidth and 3‐dB axial ratio bandwidth. From the distributions of E ‐fields in HS‐CDRA, it is observed that TM11 δ mode has been excited. To confirmed the circular polarization in proposed antenna, E ‐field distribution on different phases (φ = 0º, 90º, 180º, and 270º) have been plotted. This antenna provides measured −10 dB input impedance bandwidth of 25.94% (centered on 4.70 GHz) and 3‐dB axial ratio bandwidth in broadside direction of 17.34% (centered on 4.90 GHz). The average gain and radiation efficiency in working band are 1.56 dBi and 93.43% in broadside direction, respectively. CP radiation pattern shows that the proposed antenna has left hand circular polarization and this developed antenna could be useful for wireless applications like WLAN/Wi‐MAX bands.